Endoscopic Sphincterotomy before Fully Covered Metal Stent Placement Is Not Required for Distal Malignant Biliary Stricture due to a Pancreatic Head Tumor. (15th January 2019) - Nakahara, Kazunari; Michikawa, Yosuke; Morita, Ryo; Suetani, Keigo; Morita, Nozomi; Sato, Junya; Tsuji, Kensuke; Ikeda, Hiroki; Matsunaga, Kotaro; Watanabe, Tsunamasa; Matsumoto, Nobuyuki; Kobayashi, Shinjiro; et al.
Abstract : Background/Aims . Endoscopic sphincterotomy (EST) is often performed before fully covered self-expandable metal stent (FCSEMS) placement in order to prevent pancreatitis. However, it is not clear whether EST prevents pancreatitis or affects other adverse events (AEs). This study is conducted to evaluate the necessity of EST before FCSEMS placement for distal malignant biliary strictures due to a pancreatic head tumor. Methods . This study included 68 patients who underwent FCSEMS placement for distal malignant biliary stricture due to a pancreatic head tumor. Treatment outcomes and AEs were retrospectively compared between 32 patients with EST before FCSEMS placement (EST group) and 36 patients without EST (non-EST group). Results . The success rates of drainage for the EST and non-EST groups were 100% and 97.2%, respectively (P = 0.95 ). The incidence of pancreatitis in the EST and non-EST groups was 3.1% and 0%, respectively (P = 0.95 ). The incidence of hyperamylasemia in the EST and non-EST groups was 12.5% and 13.9%, respectively (P = 0.85 ). The incidence of all AEs in the EST and non-EST groups was 15.6% (pancreatitis: 1, cholecystitis: 2, and stent migration: 2) and 13.9% (cholecystitis: 3, stent migration: 2), respectively (P = 0.89 ). Conclusions . EST before FCSEMS placement for distal malignant biliary stricture due to a pancreatic head tumor does not affect the successful drainage and incidence of adverse events. The necessity of EST to prevent pancreatitis before FCSEMS placement was deemed low.